The role of microparticles in the transfer of pathogenic microflora in the air of orthopaedic operating rooms (review of literature) - Vasiuk, Sergey; Vasylchyshyn, Yaroslav; Vasiuk, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
The authors have analysed scientific publications, which deal with study of the role of microparticles with different size, suspended in the air of operating rooms, in transfer of pathogenic and opportunistic microflora. The authors believe that introduction of air ultrafiltration in operating rooms can become a measure for preventing intraoperative contamination of operative wounds, surgical gloves and instruments with a resultant decrease in the rate of postoperative infectious complications.